Destination image in virtual social networks (2019)
Since destination image is an important construct for tourism research, cities and regions try to understand and to develop a positive image in order to guarantee the number of visitors and the tourism revenue. The main objective of this article was to develop a model of evaluation of destination image through the use of pictures shared in virtual social networks. We propose that the image of a destination can be analyzed through the way tourists picture the destination in virtual social networks. Hence, we have developed a measurement to evaluate destination image based on pictures posted on Instagram, and we made a model to analyze destination image based on pictures shared in virtual social network. Our method was composed by an analysis of 1,500 pictures of three important destinations in Brazil (Foz do Iguaçú, Rio de Janeiro, and Salvador). Our results contribute to tourism research by indicating that it is possible to determine the main characteristics of a destination by the pictures in virtual social networks, and by providing a 5-dimension model to do so. This study contributes to tourism research in two venues. First, we propose a method for evaluating destination image based on pictures posted in social media rather than the usual questionnaires. This may help scholars by providing an alternative way of evaluating destination image without recall, social desirability and non-response bias. And secondly, this study also contributes to practitioners and public policy in tourism by showing which characteristics of a destination image are more prominent to the destination image, based on virtual social networks.